Development Law Politics in Village Authority Related to Spatial Planning in Indonesian - Gunawan, Agus; Animuntaha, Fadhila (Jurnal Penegakan Hukum dan Keadilan, 2025)
Development law significantly influences the direction of village management policies and the regulation of authority, particularly within the realm of spatial planning. Lacking an effective spatial plan hinders the optimization of regulations for sustainable development in villages, leads to conflicting regulations, and impedes local community involvement in harnessing their natural resource potential. This research employs a normative legal methodology grounded in specific methods and systematic thinking, intending to examine a phenomenon of legal issues through a sociolegal lens. The findings of the political and legal study consider village autonomy as a cohesive legal entity within a region that possesses the power to establish its administration, develop regional plans, and manage natural resources for the advantage of local populations, adhering to the principle of decentralization. The idea of village autonomy refers to the capability and initiative of the village community to independently organize and oversee the village’s potential, demonstrating its existence as a quality and self-sufficient community unit. Law Number 3 of 2024 governs the political and legal dimensions of development, assigning a strategic role to villages in executing spatial management development. Based on this law, the transparency of village authority promotes community involvement in the village spatial planning process. However, this law also has positive and negative impacts. On the one hand, it will improve the village economy because the community can manage and run their businesses independently and legally. However, the crucial implication is the loss of local community rights due to unclear derivative regulations.